DAI (DLM-1/ZBP1) as a Genetic Adjuvant for DNA Vaccines That Promotes Effective Antitumor CTL Immunity - Álvaro Lladser; Dimitrios Mougiakakos; Helena Tufvesson; Maarten A. Ligtenberg; Andrew F. G. Quest; Rolf Kiessling; Karl Ljungberg (2010)
DNA vaccination is an attractive approach to induce antigen-specific cytotoxic CD8(+) T lymphocytes (CTLs), which can mediate protective antitumor immunity. The potency of DNA vaccines encoding weakly immunogenic tumor-associated antigens (TAAs) can be enhanced by codelivering gene-encoded adjuvants. Pattern recognition receptors (PRRs) that sense intracellular DNA could potentially be used to harness intrinsic immune-stimulating properties of plasmid DNA vaccines. Consequently, the cytosolic DNA sensor, DNA-dependent activator of interferon (IFN) regulatory factors (DAI), was used as a genetic adjuvant. In vivo electroporation (EP) of mice with a DAI-encoding plasmid (pDAI) promoted transcription of genes encoding type I IFNs, proinflammatory cytokines, and costimulatory molecules. Coimmunization with pDAI and antigen-encoding plasmids enhanced in vivo antigen-specific proliferation, and induction of effector and memory CTLs. Moreover, codelivery of pDAI effectively promoted CTL and CD4(+) Th1 responses to the TAA survivin. The DAI-enhanced CTL induction required nuclear factor κB (NF-κB) activation and type I IFN signaling, but did not involve the IFN regulatory factor 3 (IRF3). Codelivery of pDAI also increased CTL responses to the melanoma-associated antigen tyrosinase-related protein-2 (TRP2), enhanced tumor rejection and conferred long-term protection against B16 melanoma challenge. This study constitutes "proof-of-principle" validating the use of intracellular PRRs as genetic adjuvants to enhance DNA vaccine potency.